THRESHOLD VALUES OF ANTIBODIES TO ESTROGEN, PROGESTERON AND BENZO[A]PYRENE AS A RISK FACTOR OF THE DEVELOPMENT OF EXTERNAL GENITAL ENDOMETRIOSIS - Наталья Владимировна Артымук; Виталий Олегович Червов; Лариса Николаевна Данилова; Елена Геннадьевна Поленок (The Publishing House Medicine and Enlightenment, 2019)
The purpose of the study - to determine the level of antibodies (AT) of Ig classes A and G to estradiol (E2), progesterone (P) and benzo[a]pyrene (Bp) in patients with endometriosis of varying severity and establish their threshold values as a risk factor for the development of external genital endometriosis. Materials and methods. A retrospective case - control study was conducted. The study included 200 women. Group I - women with external genital endometriosis (n = 100), Group II - patients with tuboperitoneal infertility (n = 100). All patients underwent an immunological study of blood serum, determined levels of steroid hormones (P, E2), antibodies to them and Bp. To identify the threshold levels of AT, a ROC analysis was performed. Results. In women with external genital endometriosis, significantly higher levels of AT IgA and IgG to E2, P and benzo[a]pyrene were detected, compared with women of group II. The threshold levels of IgA-Bp, IgA-E2 and IgA-P are > 5 UE, IgG-Bp, IgG-E2 > 9 UE and IgG-P > 8 UE. The level of IgG-P in patients with severe forms of endometriosis is statistically significantly higher than in small forms of the disease. In severe forms, there is a tendency to increase other classes of antibodies. Conclusion. Patients with external genital endometriosis are characterized by higher levels of IgA and IgG to Bp, E2, P. Their threshold values, which are risk factors for developing the disease, have been established.